EVALUACIÓN DE UN ENVASE COMESTIBLE A BASE DE PECTINA EXTRAÍDA DE LAS CÁSCARAS DE CACAO (Theobroma cacao), TORONJA (Citrus × paradisi) Y MARACUYÁ (Passiflora edulis) - Chafla Ortiz, Estefany Yesenia (2023)
The pollution generated by plastic waste from food packaging has led to the development of proposals for innovative, sustainable and attractive packaging for the market. Thus, edible packaging, in addition to being a way out of pollution, offers a unique sensory experience and can be customized to suit customer preferences. In this line, edible packaging has been developed from sustainable materials such as pectin extracted from cocoa shell (Theobroma cacao) passion fruit (Passiflora edulis) and grapefruit (Citrus × paradisi). For its development, an experimental design of Box- Behnken mixtures was used, followed by statistical and response surface analysis to develop the quadratic model and evaluate the influence of the variables studied, controlling the variables of humidity, hardness, cohesiveness and structure according to parameters of maximization, minimization, target, and the minimum cost. For this, 15 treatments were used, in the case of the acceptability index, 4 treatments and 15 repetitions were used, giving a total of 60 experimental units. The amount of flour, pectin, and sugar needed for each container was found, varying according to the quality of the pectin and the established conditions. The container with grapefruit peel pectin (EPCT) was the one with the minimum cost (0.11 cent) and the highest acceptability index (75.3 %), with good mechanical characteristics of humidity 7.88 g/100 g of sample, hardness 6.73 mm of indentation, cohesiveness 752.15 N and structure 16.77 mm of dentation after 10 min of soaking, according to a panel of semi-trained testers. The cocoa shell pectin container (EPCC) also obtained a high cost (0.10 cent) and lower acceptability, even so it achieved 53.82% acceptance. The results of the study can be used to improve the formulation of edible packaging and other similar products based on flour, water, pectin and sugar.